Innovation performance of small and medium private hospitals in India : roles of open and closed innovation - Ahmad, Sahrish (2019)
Innovation is increasingly becoming a common practice within the hospitals to improve the performance. In India, innovation among hospitals is prevalent and the healthcare services serve to more than two third of its population. Although innovation is significant among the large private hospitals, the practice of this concept is still lacking among the small and medium private hospitals. Previous research on innovation performance of healthcare organizations mostly focused on the large private hospitals, and the factors affecting innovation performance among small and medium private hospitals were neglected. Therefore, this study aims at examining the factors that affect the innovation performance of small and medium private hospitals namely open innovation and closed innovation practices. Subsequently, it is also pertinent to investigate the impact of service innovation orientation, organisational learning, and innovation culture on open innovation and closed innovation that lead to innovation performance. Further, this study also examined mediating effect of open innovation and closed innovation between service innovation orientation, organisational learning, innovation culture, and innovation performance. This study was designed as a quantitative study and data were collected at one point of time. The study used nonprobability purposive sampling technique and the data were collected from small and medium private hospitals from three states of India (Delhi, Uttar Pradesh, and Uttarakhand). Questionnaires were sent to the doctors of small and medium private hospitals through electronic mail. In total, 186 questionnaires were returned and only 173 completed questionnaire were found useful data analysis.